A new species of Naushonia Kingsley, 1897 (Decapoda: Thalassinidea: Laomediidae) from Vietnam and the Philippines with notes on the genus Espeleonaushonia Juarrero & Martinez-Iglesias, 1997 - Dworschak, Peter C.; Marin, Ivan; Anker, Arthur (Zootaxa, 2006)
Naushonia carinata n.sp. is described from five specimens collected from burrows of the largesized callianassid shrimp, Glypturus armatus (A. Milne-Edwards, 1870), in Nha Trang Bay, Vietnam, and Panglao I., Philippines. The new species differs from all other congeners by the presence of one median and two submedian carinae on first to fifth abdominal somites and broad propodi of the chelipeds. The genus Espeleonaushonia Juarrero & Martínez-Iglesias, 1997 is redefined and the cave inhabiting laomediid, Naushonia manningi Alvarez, Villalobos & Iliffe, 2000, from the Bahamas, is transferred to this genus.